Swipe, Shop, Repeat: Investigating Technology Acceptance In Indonesia’s Leading E-Commerce - Ronny H. Walean; Christian G. Siwy; Deske W. Mandagi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
With the rapid growth of e-commerce in Indonesia, understanding the factors influencing user acceptance is crucial for both platform developers and policymakers. This study examines the acceptance of Tokopedia, one of Indonesia’s leading e-commerce platforms, using Davis' Technology Acceptance Model (TAM). It aims to explore the relationships between perceived ease of use, perceived usefulness, attitude toward use, behavioral intention to use, and actual use within the TAM framework. A quantitative descriptive and correlational research design was adopted, utilizing an online survey distributed to 201 active Tokopedia users in North Sulawesi, Indonesia. The collected data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 3. The results indicate that attitude toward use and behavioral intention to use significantly influence actual use of e-commerce. Additionally, perceived ease of use positively affects both perceived usefulness and attitude toward use, while behavioral intention has the strongest impact on actual use. Furthermore, perceived ease of use and perceived usefulness influence actual use indirectly through attitude toward use and behavioral intention to use. These findings provide valuable insights for e-commerce practitioners seeking to enhance user engagement and platform adoption. By understanding the key determinants of e-commerce acceptance, businesses can develop more effective marketing strategies, improve user experience, and optimize product offerings to encourage sustained platform use.